Pyridinecarboxylic Acid Derivative Stimulates Pro-Angiogenic Mediators by PI3K/AKT/mTOR and Inhibits Reactive Nitrogen and Oxygen Species and NF-κB Activation Through a PPARγ-Dependent Pathway in T. cruzi-Infected Macrophages - Penas, Federico Nicolás; Carta, Davide; Cevey, Ágata Carolina; Rada, María Jimena; Pieralisi, Azul Victoria; Ferlin, María Grazia; Sales, María Elena; Mirkin, Gerardo A.; Goren, Nora Beatriz (Frontiers in Immunology, 2020)
Chagas disease is caused by T. cruzi infection and represents an important public health concern in Latin America. Macrophages are one of the main infiltrating leukocytes in response to infection. Parasite persistence could trigger a sustained activation of these cells, contributing to the damage observed in this pathology, particularly in the heart. HP24, a pyridinecarboxylic acid derivative, is a new PPARγ ligand which exerts anti-inflammatory and pro-angiogenic effects. The aim of this work was to deepen the study of the mechanisms involved in the pro-angiogenic and anti-inflammatory effects of HP24 in T. cruzi-infected macrophages, which have not yet been elucidated. We show for the first time that HP24 increases expression of VEGF-A and eNOS through PI3K/AKT/mTOR and PPARγ pathways, and that HP24 inhibits iNOS expression and NO release, a pro-inﬂammatory mediator, through PPARγ-dependent mechanisms. Furthermore, this study shows that HP24 modulates H2O2 production in a PPARγ-dependent manner. It is also demonstrated that this new PPARγ ligand inhibits the NF-κB pathway. HP24 inhibits IKK phosphorylation and IκB-α degradation, as well as p65 translocation to the nucleus in a PPARγ-dependent manner. In Chagas disease, both the sustained increment in pro-inflammatory mediators and microvascular abnormalities are crucial aspects for the generation of cardiac damage. Elucidating the mechanism of action of new PPARγ ligands is highly attractive, given the fact that it can be used as an adjuvant therapy, particularly in the case of Chagas disease in which inflammation and tissue remodeling play an important role in the pathophysiology of this disease.